Analisis Sistem Stok Barang Manual di Gudang PT. Indah Permata Menggunakan Metode Pieces - Maria Erince Seuk; Tupan Tri (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
Inventory management is a crucial aspect of operational activities, especially for companies engaged in distribution and warehousing. PT. Indah Permata currently implements a manual stock recording and management system in its warehouse, which relies on written logs or basic spreadsheets. This manual system creates several problems, such as data entry errors, delays in data updates, and discrepancies between physical stock and administrative records. This study aims to analyze the weaknesses of the manual inventory system using the PIECES framework, which includes six key aspects: Performance, Information, Economy, Control, Efficiency, and Service. The research method used is a qualitative descriptive approach involving observation, interviews, and the distribution of questionnaires to relevant stakeholders. The results show that the manual system performs very poorly across all PIECES aspects, with scores ranging from 1.51% to 1.65%, categorizing it as "Very Poor." These findings indicate that the current system fails to support efficient, accurate, and well-Controlled operations. Therefore, it is recommended that the company undertake digital transformation by implementing an integrated and automated inventory management Information system. This recommendation is expected to enhance work effectiveness, resource Efficiency, and overall Service quality in a sustainable manner.